Хүрэн нүүрсэнд цацраг идэвхийн тэнцвэрийг тодорхойлсон нь - Н, Норов; Ж, Ганзориг; С, Даваа (Scientific transaction of the National University of Mongolia. Physics, 2022)
This work presents the results of measurements of radionuclide concentrations and radioactivity equilibrium in brown coals of the eastern part of Mongolia. Using the gamma spectrometry method based on high-purity germanium (HP Ge) detectors, it has been found that U/Ra equilibrium is significantly disturbed ranges from 1.4:1.5 in brown coal samples. The mechanism of formats of equilibrium ratios between Natural Radioactive elements in Uraniumcontcuning coal samples are considered ...